The representation of Orhan Pamuk's novels in Brazil as (indirect) translations - Facci Torezan, Isabela (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2023)
The aim of this dissertation is to ask the following question: (how) are the books by Turkish author Orhan Pamuk representing themselves as (indirect) translations in Brazil? The methodology consists of analysing 7 novels published between 2006 and 2017 and assessing their covers and other paratextual elements in order to determine whether the books represent themselves as (indirect) translations and if so, how this is being done in terms of size, content, and organisation. By assessing the representation of indirect translations of books by a highly prestigious, Nobel Prize winner author, this dissertation aims to add to the debate about the status of contemporary literary indirect translation, an area still under researched. Key words: indirect translation; literary translation; indirect translation in Brazil; Orhan Pamuk.
Keywords: Literary Translation